2020
DOI: 10.1111/sms.13826
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of in‐school and out‐of‐school sport injury prevention: A test of the trans‐contextual model

Abstract: The current study aimed to predict secondary school students’ motivation toward sport injury prevention in “in‐school” and “out‐of‐school” contexts, and their sport injury prevention behavior at 3‐month follow‐up using the trans‐contextual model (TCM). Hong Kong secondary school students (N = 1566; mean age = 13.34 years, range = 11 to 19; female = 49.42%) were recruited. Participants were asked to complete a survey comprising previously validated scales measuring TCM constructs at baseline and a measure of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 70 publications
(151 reference statements)
4
26
0
7
Order By: Relevance
“…It is also worth noting that predicted relations among TCM model constructs were positive and statistically significant, consistent with previous studies 15,22,23,25 . Importantly, these effects used change scores which contrasts with the typical approach.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It is also worth noting that predicted relations among TCM model constructs were positive and statistically significant, consistent with previous studies 15,22,23,25 . Importantly, these effects used change scores which contrasts with the typical approach.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, individuals’ perceived need support, that is, the extent to which individuals feel that significant others support their psychological needs, is an important factor determining autonomous motivation. The positive association between perceived need support from significant others and autonomous motivation has been consistently reported in previous studies 15,26,30,35,36 . Based on this tenet, PE teachers who teach sport injury prevention in a psychological need supportive manner would be expected to facilitate students’ perceived need support and autonomous motivation toward sport injury prevention behavior 12 .…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Despite the importance that the Theory of Planned Behaviour may have in helping to understand the development and establishment of young people’s behaviors, we have no evidence of studies during the Primary Education stage, although we do have evidence of studies at the Secondary Education stage. In this regard, several studies have shown how the Theory of Planned Behaviour has been positively related to behaviors related to physical activity habits [ 27 , 28 , 29 ] and balanced eating habits [ 30 , 31 ] and negatively related to maladaptive habits, such as cigarette smoking [ 32 ].…”
Section: Introductionmentioning
confidence: 99%